Improving the performance by message broadcasting in VANETS. (2017) - Ganesh, M. Sakthi; Krishna, P. Venkata
In vehicular adhoc networks, messages are broadcast by active mobile nodes spontaneously to all the neighbourhood nodes within the connectivity range. These important messages may have severe delay and are time sensitive. The main aim of this work is to broadcast the safety message, to avoid the packet collision or to reduce the packet loss so that the efficiency of the network is improved and these can be analysed using different protocols in vehicular adhoc network. In typical carrier sense multiple accesses the users that content with channel access do not seem to be suitable for this application. Protocol sequence is the method we are following to broadcast the safety message. 0s and 1s are the protocol sequences used. When each user in the network reads the 0s and 1s they transmit the packet in the time slot. It does not require time synchronisation between the mobile nodes. We compare the delay performance with dedicated short range communication protocol, ALOHA type random access scheme, and zone routing protocol. By arranging the data packets a hard assurance of delay might be achieved. The delay in the network reduces in zone routing protocol.